Caring for Parents After the Death of a Child. (August 2018) - October, Tessie; Dryden-Palmer, Karen; Copnell, Beverley; Meert, Kathleen L.
Abstract : Objectives: To describe the health outcomes of bereaved parents and identify practical strategies for critical care providers as they support and provide anticipatory guidance to bereaved parents. Data Sources: PubMed and PsycInfo databases with search terms of bereavement, grief, with parent and pediatric or child complimented by personal experience and knowledge. Study Selection: We sought studies describing parental health outcomes and needs of bereaved parents after the death of their child. Data Synthesis: A narrative literature review was performed and framed from the perspective of PICU providers who care for bereaved parents. We aimed to describe experiences of grief and short- and long-term consequences and approaches to the care of parents and families in the immediate period and in the months after the death of a child. Conclusions: The death of a child is a traumatic experience that can put parents at risk for adverse mental and physical health during bereavement. Health professionals working in PICUs can benefit from knowing these risks to best support bereaved parents, both during their child's hospitalization and in the early postdeath period. The bereavement experience of parents is an adaptive process, and ongoing professional support may be required for vulnerable families. After the child's hospitalization and death, a bereavement follow-up meeting with PICU physician(s) and staff may allow parents to gain additional information, emotional support, and provide an opportunity for parents to give feedback on their experiences.